L’expérience du comité de rédaction scientifique dans un parcours de jeune chercheuse : rétrospective sur sept années chez DD&T - Lucie Morère; Leslie Carnoye; Rémy Petitimbert (Développement Durable et Territoires)
This interview with Lucie Morère is part of a series of exchanges conducted for the anniversary issue of Développement durable & territoires, which aims at retracing the history of the journal and to define some future perspectives. The young researcher, now a practitioner of public action, recalls the added-value of her participation to the editorial committee in the construction of her professional development. The interview highlights the double heuristic and political interest of the action-research agenda, which characterizes the journal.